The potential of light transmission using solar light tube for interior illumination in Malaysia (Building: Panasonic Semiconductor descret Malacca) - Norain Ali (School of Environmental Engineering, University Malaysia Perlis, 2012)
Solar light tubes that were installed in the building Panasonic Semiconductor Descrete, Malacca is a right of action taken by the management company in achieving green building and further towards green technology. The use of natural resources that provide the brightness of sunlight in the building without the use of electricity, it is a factor in addressing the problem of global warming is happening due to high electricity consumption while also reducing CO2 . The objective of this study was to determine the potential in the use of solar light tube, identify the level of brightness is produced and then make a comparison between the use of cost efficiency solar light tubeand electricity energy . The study was done in an office building management and operation of Panasonic Semiconductor Descrete,Malacca , as the building is the first building in Malaysia, using the technology . Interviews and questionnaires are made on the effectiveness use, level of brightness, fitness, conservation, aesthetic values and the effect of Solar light tubes. In addition, the data of observations were also made to determine the level of brightness . This information can assist in determining the effectiveness and advantages of the installation and use of Solar light tube widely in Malaysia. Results showed that although the installation would cost, but in the long term benefit are in cost installation, electricity, release of CO2 and preserve the environment. Solar light tube is the best alternative in the future to replace of electricity during the day.